Historical Analysis of Nomadic Education Programme in Kwara State, Nigeria: 1988-2011 - Abubakar, Saidu; Abudu, Zeinab; Odebode, Aminat; Jekayinfa, Oyeyemi (NIU Journal of Social Sciences, 2017)
In a bid to enhance the access of nomads to education and to translate into action the philosophy of equality of educational opportunities, the Federal Government of Nigeria introduced a special education programme called Nomadic Education in 1986. Following this, all the states of the federation with large concentration of nomadic Fulani were directed by the Federal Government to launch the programme in their respective states. Kwara state government hence, launched the programme in the state 1988. This study, therefore, traced the trends in the historical development of nomadic education in North Central Nigeria: 1988-2011. This study adopted the historical research method, relying on both primary and secondary sources. The population of the study comprised all relevant stakeholders in nomadic education programme: the officials, head teachers and nomads. A total number of 420 respondents were sampled in the study using the multi-stage sampling techniques. Challenges of Nomadic Education Questionnaire (CNEQ) was used to gather data for the study. It was revealed that students’ enrolment figures were fluctuating within the period covered by this study. It was also found out that there was an upward trend in the number of Nomadic Schools in Kwara state, Nigeria from 1988-2011. Based on the findings, it was recommended that government should also embark on constant awareness campaign to encourage and sustain enrolment in nomadic school. Keywords: Nomadic, Nomadic Education, Historical Analysis.